Relationship between different aspects of leadership and motivation - Medeiros, Aline Silveira; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2021)
Leadership is able to influence follower’s behavior, involving different aspects of their motivation. Thus, this research correlates leadership and motivation, based on questionnaires whose answers were structured by the Likert scale. Sixty-one people were interviewed, mostly aged 25 to 45 years old, working in different institutions and under different leaderships. All correlations were positive. Highest correlations, although less than 0.5, were computed between autonomy versus recognition feelings; receiving feedback versus appreciation and recognition feelings; leader control versus appreciation and recognition feelings and, finally, identification with leader’s principles versus importance feeling. Recognition and appreciation feelings tend to be stronger when there is autonomy and feedback, in addition to leadership control of who is carrying out the activities. There is also a need to identify with the leader’s principles for to develop recognition and appreciation feelings, and, especially, for valuing the work.